Analysis of ammonia-oxidizing bacteria dominating in lab-scale bioreactors with high ammonium bicarbonate loading - Vejmelkova, Dana; Sorokin, Dimitry Y; Abbas, Ben; Kovaleva, Olga L; Kleerebezem, Robbert; Kampschreur, Marlies J; Muyzer, Gerard; van Loosdrecht, Mark C M (Applied microbiology and biotechnology, 2012)
The ammonia-oxidizing bacterial community (AOB) was investigated in two types of laboratory-scale bioreactors performing partial oxidation of ammonia to nitrite or nitrate at high (80 mM) to extremely high (428 mM) concentrations of ammonium bicarbonate. At all conditions, the dominant AOB was affiliated to the Nitrosomonas europaea lineage as was determined by fluorescence in situ hybridization and polymerase chain reaction in combination with denaturing gradient gel electrophoresis. Molecular analysis of the mixed populations, based on the 16S rRNA and cbbL genes, demonstrated the presence of two different phylotypes of Nitrosomonas, while microbiological analysis produced a single phylotype, represented by three different morphotypes. One of the most striking features of the AOB populations encountered in the bioreactors was the domination of highly aggregated obligate microaerophilic Nitrosomonas, with unusual cellular and colony morphology, commonly observed in nitrifying bioreactors but rarely investigated by cultural methods. The latter is probably not an adaptation to stressful conditions created by high ammonia or nitrite concentrations, but oxygen seems to be a stressful factor in these bioreactors.
Keywords: Ammonia; Nitrates; ribozomální DNA; DNA, Ribosomal; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA bakterií; bakteriální proteiny; dusitany; společenstvo; Bacterial Proteins; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; Molecular Sequence Data; Biota; Culture Media; Phylogeny; oxidace-redukce; molekulární sekvence - údaje; Bicarbonates; kultivační média; Oxidation-Reduction; Nitrosomonas; Sequence Analysis, DNA; hybridizace in situ fluorescenční; Bioreactors; sekvenční analýza DNA; dusičnany; In Situ Hybridization, Fluorescence; Cluster Analysis; hydrogenuhličitany; fylogeneze; amoniak; RNA ribozomální 16S; bioreaktory; Nitrites